Applications in utilizing soil gas geochemistry along with geological and geophysical data to construct helium exploration statistical models - Halford, D. T.; Karolytė, R.; Dellenbach, J. T.; Cathey, B.; Cathey, M.; Balentine, D.; Andreason, M. W.; Rice, G. K. (Frontiers in Earth Science, 2024)
A key challenge in helium (He) exploration is determining the efficacy of surficial soil gas surveys. While soil gas surveys can detect helium, the mechanisms leading to these signals are often poorly understood, hindering reliable interpretation for exploration purposes. Here we present the results of seven new He soil gas surveys (n = 1974) at the Akah Nez Field, Beautiful Mountain Field, Porcupine Dome area, Rattlesnake Field, Tom area, Tohache Wash area, and White Rock area, on the Colorado Plateau, Four Corners area, United States. Utilizing 2D seismic, well logs, and geophysical potential field data, structural maps were constructed of potential He reservoirs at depth and relationships were examined. Given geospatial relationships are being examined using the soil gas survey data, it is important to understand the mechanism that allows subsurface He to migrate upwards into the soil. In several fields interpreted basement faults act as migration conduits from the basement to the surface (i.e., leaky reservoir seals), and in other cases there is evidence for reservoir flank/crest fracturing likely due to differential compaction. Based on the regional geologic history, advective systems are likely responsible for the observed He soil gas signatures. Additionally, based on the Tohache Wash data (most prospective He area) an effective and risk-reducing novel technique is presented that constructs a predictive He exploration model utilizing soil gas geochemistry, high-resolution geophysical data, well data and seismic data using Bayesian ANOVA techniques, which may be translated to areas outside of the Four Corners area, United States.